Management of resistant de Quervain tenosynovitis with local anesthetic (neural therapy): A case report - Bölük Şenlikci, Hüma; Yılmaz, Özden; Nazlıkul, Hüseyin (Journal of Surgery and Medicine, 2020)
De Quervain tenosynovitis is the most common reason of lateral wrist pain. Treatment consists of splinting, non-steroid anti-inflammatory drugs, and corticosteroid injections. Neural therapy (NT) is a treatment modality using injections with local anesthetics for diagnosis and treatment. Musculoskeletal disorders can be cured by NT. We herein present the management of resistant de Quervain tenosynovitis by neural therapy in a 45-year-old male patient, who was referred to our outpatient clinic with the complaint of right wrist pain lasting over 2 years. His pain was 7/10 based on visual analog scale which had gradually increased. The patient also stated that he could not lift bags and had experienced neck pain 2 years ago. He was engaged in the neural therapy program with the diagnosis of cervical discopathy and tenosynovitis. After 3 sessions he had improvement in functional outcome and pain. In the treatment of resistant de Quervain tenosynovitis accompanying cervical discopathy, neural therapy is an effective and safe method.